PENGENALAN APLIKASI JIRA DALAM MANAJEMEN PROYEK DI SMK YPKK 1 SLEMAN, YOGYAKARTA - Rudy Ansari; Rudy Ansari; Irwansyah Irwansyah; Irwansyah Irwansyah; Nia Ekawati; Nia Ekawati; Herman Herman; Sunardi Sunardi (PUAN INDONESIA, 2026)
The community service activity at SMK YPKK 1 Gamping aims to align the vocational education curriculum with industry standards through the introduction of Agile and Scrum methods using the JIRA application. The main challenge faced was the students' lack of understanding of professional project management tools, so this training focused on mastering JIRA features such as Scrum/Kanban boards and issue tracking. Through training and mentoring of 30 students, there was a significant increase in competence. Data shows that the highest score on the pre-test was 80 (9 participants), which then increased on the post-test to a perfect score of 100 achieved by 15 participants. The evaluation results concluded that 50% of participants had achieved the maximum level of understanding in operating JIRA. Thus, this implementation successfully bridged the gap between academic theory and the practical needs of the workplace, while equipping students with globally relevant project management skills.